Sexual shape dimorphism accelerated by male–male competition, but not prevented by sex‐indiscriminate parental care in dung beetles (Scarabaeidae). Issue 14 (19th June 2015) - Kishi, Shigeki; Takakura, Koh‐Ichi; Nishida, Takayoshi
Abstract Dimorphic sexual differences in shape and body size are called sexual dimorphism and sexual size dimorphism, respectively. The degrees of both dimorphisms are considered to increase with sexual selection, represented by male–male competition. However, the degrees of the two dimorphisms often differ within a species. In some dung beetles, typical sexual shape dimorphisms are seen in male horns and other exaggerated traits, although sexual size dimorphism looks rare. We hypothesized that the evolution of this sexual shape dimorphism without sexual size dimorphism is caused by male–male competition and their crucial and sex‐indiscriminate provisioning behaviors, in which parents provide the equivalent size of brood ball with each of both sons and daughters indiscriminately. As a result of individual‐based model simulations, we show that parents evolve to provide each of sons and daughters with the optimal amount of resource for a son when parents do not distinguish the sex of offspring and males compete for mates. This result explains why crucial and sex‐indiscriminate parental provisioning does not prevent the evolution of sexual shape dimorphism. The model result was supported by empirical data of Scarabaeidae beetles. In some dung beetles, sexual size dimorphism is absent, compared with significant sexual size dimorphism in other horned beetles, although both groups exhibit similar degrees of sexual shape dimorphism in male horns and other exaggerated traits.